Purifying Selection in the Toll-Like Receptors of Song Sparrows Melospiza melodia. (9th June 2018) - Nelson-Flower, Martha J; Germain, Ryan R; MacDougall-Shackleton, Elizabeth A; Taylor, Sabrina S; Arcese, Peter
Abstract: Variation in immune gene sequences is known to influence resistance to infectious diseases and parasites, and hence survival and mate choice, across animal taxa. Toll-like receptors ( TLR s) comprise one essential gene family in the vertebrate innate immune system and recognize evolutionarily conserved structures from all major microorganism classes. However, the causes and consequences of TLR variation in passerine birds remain largely unexplored. We examined 7 TLR genes in song sparrows ( Melospiza melodia ), a species that is studied across North America. We then examined sequences from 4 unduplicated TLR s ( TLR1LB, TLR3, TLR4, and TLR15 ) from birds in 2 parts of the species' range ( N = 27, N = 6), tested for evidence of selection, and conducted pilot analyses of the role of TLR heterozygosity in survival. We identified 45 SNPs: 19 caused changes in amino acid sequences and 2 of these were likely deleterious. We found no evidence of codon-level episodic positive selection but detected purifying selection at codons in all TLR s. Contrary to expectations we found no strong correlation between heterozygosity at TLR s and inbreeding coefficient f (estimate ± standard error [SE] = −0.68 ± 0.37, R adj 2 = 0.08, F 1, 25 = 3.38, P = 0.08). In addition, pilot analyses revealed no relationship between TLR heterozygosity and survival (β ± SE: 0.09 ± 2.00, P = 0.96), possibly due to small sample size. Further analyses of genetic diversity in TLR s are likely to advance understanding of the effects of innate immune gene diversity on the fitness and persistence of wild populations.